The relationship between subjective social class and pro-social behavior: the mediating role of self-control and the dual-edged sword effect of shame - Zheng, Jiaqi; Liu, Haoliang; He, Zhifang (Frontiers in Psychology, 2025)
IntroductionPro-social behavior is a widespread behavior in life that is beneficial to others and society. Previous research has focused on the influence of individual characteristics on pro-social behavior. The rise of social class psychology has provided a new perspective for the study of pro-social behavior. It has been shown that social class has an effect on pro-social behavior, but the mechanisms behind it have not been explored enough. This study explored in depth the mechanism of the influence of subjective social class on pro-social behavior.MethodsStudy 1 examined the moderating effect of shame-proneness using a questionnaire with 312 subjects. Study 2 recruited 257 participants for an experimental study to examine the moderating effect of state shame.Results(1) subjective social class positively predicted pro-social behavior. (2) Self-control partially mediated the relationship between subjective social class and pro-social behavior. (3) Both shame-proneness and state shame negatively moderated the relationship between self-control and pro-social behavior. These findings provided valuable insights for encouraging college students to be more prosocial, which is crucial for enhancing their moral standards and fostering a harmonious society.ConclusionThis study provides theoretical support for the causes and mechanisms behind the influence of subjective social class on pro-social behavior and has practical implications for the promotion of pro-social behavior.